using the property of equality what first step would you take to rearrange the formula y = mx + b using x as the quantity of interest

1 answer

To rearrange the formula \( y = mx + b \) for \( x \) as the quantity of interest, you would first isolate the term containing \( x \). Here are the steps:

  1. Subtract \( b \) from both sides to move it to the left side: \[ y - b = mx \]

  2. Divide both sides by \( m \) to solve for \( x \): \[ x = \frac{y - b}{m} \]

Now, \( x \) is expressed in terms of \( y \), \( b \), and \( m \).